Perawatan Pasien Stroke Dengan Terapi Komplementer Dan Alternatif Di Rumah: Studi Fenomenologi - Susanti, Risqi Wahyu; Baeda, Abd Gani; Saputri, Ekawati (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
A stroke is a brain attack that can result in disability. It is scarce to know the integration between complementary and alternative therapy into conventional treatment for stroke survivors. Indonesia has various complementary and alternative therapies due to the length of the country then it is necessary to know any types of complementary and alternative therapy used by patients. The study aims to explore the treatment of stroke patients using complementary and alternative therapies. The qualitative design with a phenomenological approach was used. Data were collected through in-depth interviews with eight families with stroke survivors according to the inclusion criteria and using source triangulation. The sampling technique used was purposive sampling. A selective analysis approach and focus are used for data analysis. Results showed there were three themes derived including types of complementary and alternative therapy, method of manufacture, method of administration, and therapeutic dose. Types of complementary and alternative therapies used by the participant include herbal therapy, massage, exercise, magnetic therapy, light therapy, thalassotherapy, electrical stimulation, and diet. Further research is needed to test the effectiveness, dosage, and safety procedures to combined with conventional treatment.